Revitalizing Urban Interfaces through Historical Spaces: An Exemplification from the Renovation of Pukou Railway Station Area, Nanjing, China - Chen, Yuheng; Wu, Yanming; Qi, Zhou (International Journal of Architectural Engineering Technology, 2023)
This research delves into the significance and methodological approaches concerning the conservation and regeneration of historical facilities and spaces in contemporary urban environments through the lens of the conservation and regeneration project of the Pukou Railway Station Historic District in Nanjing. The study underscores the imperative of respecting, protecting, and revitalizing historical facilities and spaces. The refurbishment of old facilities, employing the most apt technologies and methods, accomplished a commendable balance between economic investment and efficiency. Respecting all historical textures and contexts is foundational to the preservation of the historical appearance of districts. The project, through the refurbishment of historical buildings and cautious design of new constructions, ensured a harmonious coexistence of old and new elements, thereby enhancing the cultural essence of the historical district architecture. The conservation and regeneration project of the Pukou Railway Station Historic District in Nanjing offers a beneficial case on managing historical facilities and spaces, showcasing how, through rational technical measures and respect for historical context, historical spaces can be revitalized, providing rich cultural and spatial resources for modern cities.